Penerapan Digital Marketing pada Usaha Piscok 3Z Lumer - Asmira, Lili; Dwi Astuti (Politeknik Kampar, 2025)
The aim of this digital marketing implementation project at the Piscok 3Z Lumer business is to analyze the application of the marketing mix strategy that has been carried out by Piscok 3Z Lumer, to apply digital marketing, and also to analyze the obstacles and solutions in the process of implementing digital marketing. The method used is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), and STP analysis (Segmenting, Targeting, Positioning). The digital marketing strategy implemented includes the use of social media (WhatsApp Business, Facebook, and Istagram), the creation of a Google My Business account and also the utilization of the Maxim Merchant Marketplace. The results of this project show that there is a significant increase related to promotions carried out through social media so that Piscok 3Z Lumer is increasingly recognized. However, this is inseparable from the obstacles faced such as the internet network that is often unstable which causes obstruction in the process of creating content and uploading promotional content to social media, and limited ideas for creating interesting content. The solution is to find another provider with a more stable network and look for references in various sources related to interesting content ideas.